The failure rate in reliability: numerical treatment. (1997) - Cocozza-Thivent, Christiane; Kalashnikov, Vladimir
Abstract : This paper contains approximations and bounds of failure rate functions of redundant systems. We illustrate properties of these bounds and their accuracy.